2005
DOI: 10.1038/nri1632
|View full text |Cite
|
Sign up to set email alerts
|

NFAT proteins: key regulators of T-cell development and function

Abstract: Since the discovery of the first nuclear factor of activated T cells (NFAT) protein more than a decade ago, the NFAT family of transcription factors has grown to include five members. It has also become clear that NFAT proteins have crucial roles in the development and function of the immune system. In T cells, NFAT proteins not only regulate activation but also are involved in the control of thymocyte development, T-cell differentiation and self-tolerance. The functional versatility of NFAT proteins can be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,316
2
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,347 publications
(1,353 citation statements)
references
References 132 publications
21
1,316
2
14
Order By: Relevance
“…Indeed, Dectin-1 induces the expression of genes such as IL-2 and COX-2 in an NFAT-dependent fashion [28,29]. The activation of NFAT is tightly regulated by calcium.…”
Section: Dectin-1 Requires Plcc2 For Ap-1 Nf-jb and Nfat Activationmentioning
confidence: 99%
“…Indeed, Dectin-1 induces the expression of genes such as IL-2 and COX-2 in an NFAT-dependent fashion [28,29]. The activation of NFAT is tightly regulated by calcium.…”
Section: Dectin-1 Requires Plcc2 For Ap-1 Nf-jb and Nfat Activationmentioning
confidence: 99%
“…T-cell receptor (TCR) engagement in naïve T cells initiates changes in gene expression that are essential for the generation of effector T cells. They require the activation of transcription factors, primarily NF-kB and NFAT [2,3]. TCR/CD28-induced NF-kB activation characteristically elicits the expression of both IL-2 and IL-2 receptor a chain together with the antiapoptotic molecule Bcl-x L [2].…”
Section: Introductionmentioning
confidence: 99%
“…Activated NFAT migrates into the nucleus, where it binds to and activates the promoters of several genes, including IL-2 (Ca 2+ -NFAT pathway) ( Figure 5). [80][81][82] Although a total of three isoenzymes of ITPK proteins (ITPKA, ITPKB, and ITPKC) are known to date, the importance of ITPKC in the immune system has not been identified. We investigated mRNA expression of ITPKC in a variety of tissues and revealed that ITPKC was strongly induced in stimulated peripheral blood mononuclear cells (PBMCs).…”
Section: Identification Of Itpkc As a Susceptibility Gene For Kdmentioning
confidence: 99%